2016
DOI: 10.1007/s00266-015-0599-0
|View full text |Cite
|
Sign up to set email alerts
|

Buttock Lifting with Polypropylene Strips

Abstract: This journal requires that the authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Moreover, various studies using threads have reported the effectiveness and lasting duration of the buttock lifting procedure. [11][12][13] de Benito and Pizzamiglio 12 described buttock lifting using silhouette sutures; approximately 80% of patients had stable and satisfactory results 6 months postoperatively, and they were still happy with the procedure after 1 year. Rico and colleagues 13 described buttock lifting with polypropylene strips and obtained good aesthetic results without complications for up to 8 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, various studies using threads have reported the effectiveness and lasting duration of the buttock lifting procedure. [11][12][13] de Benito and Pizzamiglio 12 described buttock lifting using silhouette sutures; approximately 80% of patients had stable and satisfactory results 6 months postoperatively, and they were still happy with the procedure after 1 year. Rico and colleagues 13 described buttock lifting with polypropylene strips and obtained good aesthetic results without complications for up to 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] de Benito and Pizzamiglio 12 described buttock lifting using silhouette sutures; approximately 80% of patients had stable and satisfactory results 6 months postoperatively, and they were still happy with the procedure after 1 year. Rico and colleagues 13 described buttock lifting with polypropylene strips and obtained good aesthetic results without complications for up to 8 years. They determined that additional surgery is important for improving the shape of the buttock because both buttock lifting and buttock shape improvements are the goals of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation